HYPERPIESIS OF CHILDREN AND TEENAGERS: REAL PROBLEM FOR A PEDIATRICIAN - L.P. Zharkova (Voprosy Sovremennoj Pediatrii, 2006)
The authors have conducted multicentric epidemiological research in 13 cities of russia to examine approaches of pediatricians to diagnostics and treatment hyperpiesis in childhood, which allowed the researchers to estimate their experience and knowledge. It has turned out that most pediatricians can not apply the knowledge in hyperpiesis diagnostics due to the absence of the agebdependent cuffs to measure hyperpiesis, as well as the skills to assess the hyperpiesis measurement findings along with centile tables use. Quality improvement of hyperpiesis diagnostics in childhood is possible by means of implementation of educational programs for the pediatricians on diagnostics and treatment of children, suffering from hyperpiesis.Key words: child's hyperpiesis, epidemiology, diagnostics, children.